Validation of Finnish Diabetes Risk Score Indonesia Version in Yogyakarta - Putri Pertiwi; Dyah Aryani Perwitasari; Satibi Satibi (Borneo Journal of Pharmacy, 2021)
Diabetes mellitus (DM) has developed as a major public health problem in the world. It is estimated that around 50% of diabetics have not been diagnosed in Indonesia, and only two-thirds of those diagnosed are undergoing treatment. This condition must be prevented. The purpose of this study was to determine the validity and reliability of the Indonesian version of the Finnish Diabetes Risk Score (FINDRISC) as an instrument for predicting type 2 diabetes mellitus (T2DM). This study was an observational study with a cross-sectional design on 60 research subjects who were indigenous people of Yogyakarta who live in Yogyakarta, which can be proven by Identity Cards by the inclusion and exclusion criteria. Validity was tested by the validity of criteria by type while using the area under the receiver-operating curve (ROC-AUC). In contrast, reliability was tested by internal consistency using Cronbach's alpha. The results showed that as many as 14 people or 23.33% experienced uncontrolled fasting blood sugar and 15 people had a risk score of FINDRISC more than 10. Based on the ROC AUC analysis, the value of 0.935 (95% CI 0.865 1.00) with a cut-off point of 10 with the value of Sn = 85%, Sp = 95%, PPV = 85%, NPV = 95%, +LR = 5.66, and -LR = 0.15. Based on the reliability test, the Cronbach's alpha value of 0.727 was obtained. The FINDRISC questionnaire is categorized as valid and reliable so that it can be a screening tool for understanding.